Parthenolecanium сorni Bouche on black currant - Bakalova, A.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
Among the dominating phytophages on black currant the most common and dangerous is Parthenolecanium сorni, the number of which is systematically increase than EPSH in 2 times which is significantly affecting the productivity of the plants. The efficiency of timely protection measures is a black currant by insecticides providing increased technical efficiency from 69.7 to 91.5%. The yield of berries herewith increases from 1.4 to 2.3 t/ha, the net income increases up to 25991 UAH/ha, and rate of energy efficiency ranging from 1.46 to 1.96 units.